Implementation of Total Quality Management (TQM) in Meeting Customer Satisfaction in Educational Institutions - Fizian Yahya; Nita Sunarya Herawati (Global Action and Education for Society, 2025)
This research discusses the implementation of Total Quality Management (TQM) in educational institutions. Using a qualitative approach, this article examines the implementation of Total Quality Management (TQM). Total Quality Management (TQM) becomes important to implement because it encompasses a continuous and comprehensive improvement process. This paper uses a literature review method discussed in the form of argumentation and descriptive narration. This literature study research shows that to achieve the best quality, this research indicates that Quality is an indicator of the success of educational institutions as well as a strategic tool for continuous improvement. The article also emphasizes the importance of good quality in the world of education, stakeholder involvement thru Total Quality Management (TQM) planning as a systematic approach to meeting standards in improving the quality of education into more effective and efficient educational services. Thus, focusing on the implementation of Total Quality Management (TQM) enables educational institutions to enhance their competitiveness and produce graduates who are relevant to the demands of the times.